Perspektif Orang Kristen Tentang Beladiri - Rudi Kurosawa; Iskak Sugiyarto (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
Self-defense is still a matter of debate among Christians, some agree and some disagree. This is because there are no references to Bible verses that directly explain this. Including the lack of studies on self-defense from a Christian perspective. This research wants to find out how Christians view self-defense. In it, are Christians allowed to participate in martial arts, be allowed to become martial arts trainers, and give tithes from their work as martial arts trainers? The research was conducted using qualitative methods, which collected data by interviewing Christians. As a result of the research, the informants were of the opinion that self-defense can be practiced by Christians as long as there is no mystical element. Christians may become martial arts trainers, and may tithe the proceeds of their work as martial arts trainers.